Secrets Between Different Kinds of Friends: Canada’s Wartime Exchange of Scientific Military Information with the United States and the USSR, 1940‑1945 - Avery, Donald (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1986)
AbstractThe outbreak of the Second World War, with the emphasis on new weapons and defence technology, brought about dramatic changes in the role of the scientist in Britain, the United States, and Canada. In many ways, Canadian scientists were most affected by these changes. Now, through the National Research Council and various defence agencies, they were able to gain access to highly confidential scientific data through the medium of joint British and Canadian research projects. Equally important was the extent that the British connection made it possible for Canadian scientists to become involved in sophisticated American military projects. Canada was also indirectly affected by the complex negotiations between Britain, the United States and the USSR on applied science exchanges during World War II. In addition, there were a variety of bilateral arrangements between Canada and the Soviet Union which had important implications for the exchange of military technology. But even more important were the revelations in September 1945 that the Soviet Union had been operating an extensive espionage system in Canada which had obtained considerable “Top Secret” scientific military information. The subsequent report of the Royal Commission on Espionage had major national and international ramifications.